2021
DOI: 10.1093/jas/skab302
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, energy content and amino acid digestibility in cyperus esculentus co-products fed to growing pigs

Abstract: This study was conducted to determine the chemical composition, DE, ME and NE contents, and the apparent and standardized ileal digestibility (AID and SID) of AA in cyperus esculentus co-products fed to growing pigs. The 5 cyperus esculentus co-products included expeller-pressed cyperus esculentus cake (EPCC), cold-pressed cyperus esculentus cake (CPCC), solvent-extracted cyperus esculentus meal (SECM), cyperus esculentus distillers’s dried grains with solubles (CE DDGS) and cyperus esculentus meal (CEM). In E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This was because the contents of various amino acids were significantly greater in diets supplemented with R1 and R2 than those in control diets ( Table 1 ). The Ile and Arg contents in beef from the R1 and R2 groups were higher than those in the control group, but the difference was not significant, indicating that different amino acids in feed have varied conversion efficiencies ( 37 ). Another possible reason is that FMDG contain probiotics that bind with epithelial cells of stomach and bowels and help to synthesize the amino acids which result in improving the content of amino acids in beef ( 15 , 38 , 39 ).…”
Section: Resultsmentioning
confidence: 95%
“…This was because the contents of various amino acids were significantly greater in diets supplemented with R1 and R2 than those in control diets ( Table 1 ). The Ile and Arg contents in beef from the R1 and R2 groups were higher than those in the control group, but the difference was not significant, indicating that different amino acids in feed have varied conversion efficiencies ( 37 ). Another possible reason is that FMDG contain probiotics that bind with epithelial cells of stomach and bowels and help to synthesize the amino acids which result in improving the content of amino acids in beef ( 15 , 38 , 39 ).…”
Section: Resultsmentioning
confidence: 95%
“…Dry matter (DM), CP, crude ash, ether extract (EE), stachyose, raffinose, maltose, sucrose, AA, and mineral levels in samples were analyzed as described previously [ 13 ]. Gross energy (GE) was analyzed according to a previous report [ 14 ]. Crude fiber (CF), neutral detergent fiber (NDF), acid detergent fiber (ADF), insoluble dietary (IDF), and soluble dietary fiber (SDF) levels were also analyzed as described previously [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The chemical composition and digestibility of tiger nut by-products obtained by different oil extraction methods (expeller-pressing, cold-pressing and solvent method) were compared. Results showed that the expeller-pressed tiger nut cake was the better feed for growing pigs compared with other two methods from the perspective of energy contents and amino acid digestibility ( Wang et al, 2021 ).…”
Section: By-products Of Tiger Nut Oil Processingmentioning
confidence: 99%
“…In addition, globulin (4.7%) and prolamin (3.8%) were also found ( Kizzie-Hayford et al, 2015 ). Although the protein content of tiger nut is not high, it contains eight essential amino acids required for human body, which makes it have the commercial value ( Wang et al 2021 ).…”
Section: By-products Of Tiger Nut Oil Processingmentioning
confidence: 99%